Pedestrians’ psychological preferences for urban street lighting with different color temperatures - Hao, Xinyi; Zhang, Xin; Du, Jiangtao; Wang, Meichen; Zhang, Yalan (Frontiers in Psychology, 2022)
White LEDs, which have been widely used in the urban street lighting, are increasingly applied to replace traditional HPS lamps with a lower CCT (correlated color temperature). Generally, studies on the CCT of street lighting focus on providing safe functional lighting for vehicle drivers. However, it is still unknown how the street light color can affect pedestrians’ perception and preferences with respect to lighting levels and ambient temperature. In this study, a wide range of CCTs (1600–5400 K) was measured for urban street lighting in Beijing, China, for example. And the transition from traditional HPS lamps to LEDs lacks a reference street lighting standard for CCT. The study aims to conduct a cross-sensory test to evaluate urban street lighting with multiple combinations of CCT values and illuminance levels according to pedestrians’ visual perception and psychological preferences. Eighteen night street lighting scenes with six CCT values and three illuminance levels were first selected in Beijing city, and then HDR videos of these scenes were taken from the view of pedestrians to conduct psychological experiments in an indoor environment with three ambient temperatures. 77 university students (24 males) were invited to assess videos of the eighteen lighting scenes in terms of seven factors, such as lighting brightness, color temperature sensation, light color preference, sense of safety, recognition, comfort, and overall preference. Several key findings were achieved as follows. (1) The CCT of urban street lighting can have significant effects on the visual psychological perceptions of participants. (2) There was a significant interaction between CCT, illuminance, and ambient temperature on the visual psychological performances of participants. (3) The higher ambient temperature will deliver the higher level of overall preference for the street lighting with medium and high CCT, and the perception of warmer light color. (4) There was a strong correlation found between participants' light color preference, comfort, and overall preferences.